2014
DOI: 10.1371/journal.pone.0092946
|View full text |Cite
|
Sign up to set email alerts
|

Deep Profiling of the Novel Intermediate-Size Noncoding RNAs in Intraerythrocytic Plasmodium falciparum

Abstract: Intermediate-size noncoding RNAs (is-ncRNAs) have been shown to play important regulatory roles in the development of several eukaryotic organisms. However, they have not been thoroughly explored in Plasmodium falciparum, which is the most virulent malaria parasite infecting human being. By using Illumina/Solexa paired-end sequencing of an is-ncRNA-specific library, we performed a systematic identification of novel is-ncRNAs in intraerythrocytic P. falciparum, strain 3D7. A total of 1,198 novel is-ncRNA candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Also, in P. falciparum ncRNAs have been associated with regulation of virulence genes (31,32). Various ncRNA transcripts have been detected by different methods (3337). Telomeres produce long ncRNAs that localize to a distinct nuclear compartment that does not overlap with telomere clusters (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in P. falciparum ncRNAs have been associated with regulation of virulence genes (31,32). Various ncRNA transcripts have been detected by different methods (3337). Telomeres produce long ncRNAs that localize to a distinct nuclear compartment that does not overlap with telomere clusters (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, little is known about its control beyond the epigenetic regulation of multigene families such as var , stevor , and rifin [ 7 , 8 ] and the specialized regulatory roles of some of the 27 putative ApiAP2 transcription factors [ 9 , 10 ]. Moreover, recent high throughput sequencing studies have shown that >80 % of the parasite genome is pervasively transcribed in a monocistronic manner during the IDC [ 11 , 12 ], hinting at robust post-transcriptional regulation to fine-tune stage-specific IDC expression. Such a mode of regulation is further supported by an enrichment of genes predicted to encode RNA-binding proteins (RBPs) in the P. falciparum genome [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep sequencing of RNA from intraerythrocytic P. falciparum developmental stages has revealed a collection of novel intermediate-size ncRNAs, including novel snoRNAs and unclassified small RNAs. Many of these unclassified RNAs are conserved among different Plasmodium species and are differentially expressed between early and late intraerythrocytic stages [69]. Additionally, a potential novel class of sncRNAs derived from tRNA fragments was revealed in P. falciparum [68].…”
Section: Small Ncrnas In Apicomplexan Parasitesmentioning
confidence: 99%